(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2023)
Human capital is the main wealth and the most valuable resource of any society, also the main factor of socio-economic progress. The problem of studying human, the formation of human capital, his total creative qualities and abilities, investments in human capital is one of the main and central problems of world science. In this article considering the some organizational and economic factors which are affecting to human capital and summarizes international experience for human capital development stimulation.